Fraud detection in web transactions - Lima, Rafael Alexandre França de; Pereira, Adriano César Machado (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
The volume of electronic transactions has raised a lot in last years, mainly due to the popularization of e-commerce. We also observe a significant increase in the number of fraud cases, resulting in billions of dollars losses each year worldwide. Therefore it is important and necessary to develop and apply techniques that can assist in fraud detection, which motivates our research. This work aims to apply and evaluate computational intelligence techniques to identify fraud in electronic transactions, more specifically in credit card operations, using Bayesian Networks and Logistic Regression. In order to evaluate the techniques, we define a concept of economic efficiency and apply them in an actual dataset of the most popular Brazilian electronic payment service. Our results show good performance in fraud detection, presenting gains up to 35.61% compared to the actual scenario of the company.